Kubismus : Künstler - Themen - Werke 1907-1920. (Köln : Josef-Haubrich-Kunsthalle, 1982)
Archipenko, Alexander ; Blanchard, Marie ; Braque, Georges ; Czaky, Joseph ; Delaunay, Robert ; Derain, André ; Duchamp-Villon, Raymond ; Dufy, Raoul ; Gleizes, Albert ; Gris, Juan ; Herbin, Auguste ; etc.
Kubismus Künstler - Themen - Werke 1907-1920, Josef-Haubrich-Kunsthalle, Lausanne, 26. Mai bis 25. Juli 1982
boek